Fitness tracker mobile application for calisthenics exercises / Aiman Harith Zaharudin ... [et al.] - Zaharudin, Aiman Harith; Jamaluddin, Muhammad Nabil Fikri; Abd Halim, Iman Hazwam; Mohd Fuzi, Mohd Faris; Syamsul Hamid, Ros (UiTM Cawangan Perlis, 2023)
Living in a world of hectic schedule between work and personal life has made many individuals difficult to find time for exercising and keep track their fitness progress. Memberships for gym nowadays is costly and even hiring a personal trainer is not everyone can afford. Due to these challenges, this paper introduces a fitness tracker mobile application named iCalFit that assists users in managing their calisthenics exercises routine and encourage individuals to engage in exercises despite their constrained time and resources. The application provides guides for calisthenics exercises, tracking users' exercises, its calorie loss and reminders. Development methodology involved three main phases which are requirement identification, design and development, and testing. The assessment of the mobile application is based on technology acceptance model, that considers three main components: Intention of Use (IU), Perceive Usefulness (PU) and Attitude (A). The questionnaire covers 15 questions distributed over to 31 randomly selected participants. PU had gained highest score out of three components, proven that the mobile application developed is efficient and capable of assisting user during exercise routine. The development of iCalFit is believed that it can solve individuals with limited fitness opportunities and drives for a healthy lifestyle.